Design of Metamaterial Antenna Based on the Mathematical Formulation of Patch Antenna for Wireless Application - S. Prasad Jones Christydass; S. Suresh Kumar; V. S. Nishok; R. Saravanakumar; S. Devakirubakaran; J. Deepa; K. Sangeetha (International Journal of Antennas and Propagation)
For WLAN/WIMAX applications, a brand-new tree-shaped metamaterial-loaded microstrip antenna is suggested. The reduced ground plane size and 4.4 dielectric constant (r) and 0.02 loss tangent (δ) dielectric are used to manufacture the 15 × 16 × 1.6 mm3 microstrip antenna. Two X-shaped slots are added to achieve the characteristics needed for WIMAX applications at 5.5 GHz. Additionally, a split-ring resonator is added to the structure to increase its bandwidth. It runs for WLAN applications with a center frequency of 5.8 GHz. The proposed structure’s measured impedance bandwidth is 45.39% with SRR and 53.48% without SRR, respectively. The proposed antenna is capable of satisfying the major requirements of modern wireless devices such as multiband operation, compact size, large bandwidth, and planar structure. The best outcomes are attained with the aid of parametric analysis of feed width, ground height, and slot width. All electromagnetic simulations were performed using CST Studio software. The measured results and the simulation agree. The waveguide extraction approach is used to demonstrate the SRR’s permeability property. The suggested antenna had adequate impedance matching, was small, and had a wide bandwidth.